ВЛИЯНИЕ АНТАГОНИСТОВ АЛЬДОСТЕРОНА НА ПАРАМЕТРЫ ЭЛЕКТРОКАРДИОГРАММЫ ВЫСОКОГО РАЗРЕШЕНИЯ У ПАЦИЕНТОВ С ПАРОКСИЗМАЛЬНОЙ ФОРМОЙ ФИБРИЛЛЯЦИИ ПРЕДСЕРДИЙ - Н. Т. Ватутин; А. Н. Шевелёк; Е. В. Ещенко; И. Н. Кравченко (Архивъ внутренней медицины)
Background. The P-wave signal-averaged electrocardiogram (SAECG) abnormalities is noninvasive marker of atrial conduction delay and predictor of paroxysmal atrial fibrillation (AF). Aldosterone antagonists used as upstream AF therapy may be effective in prevention of AF episodes, but their impact on the P-wave SAECG has not been studied. Purpose. The study aims to investigate the effect of aldosterone antagonists on the P-wave SAECG in patients with paroxysmal AF. Material and methods. The study included 58 patients with coronary heart disease and compensated chronic heart failure with preserved left ventricular systolic function (ejection fraction ≥ 45%) who had a history of paroxysmal AF and sinus rhythm at baseline. All patients received ACE inhibitors, β-blockers, statins, antithrombotic and antiarrhythmic drugs and were randomly assigned to either standart therapy only (control group, 30 patients) or aldosterone antagonist spironolactone 25 mg (spironolactone group, 28 patients) added to standart treatment. The SAECG was obtained at sinus rhythm at the baseline and after 6 months treatment. The atrial late potentials (ALP) were defined as total filtered P-wave duration of ≥125 ms and a root-mean-squared voltage of the terminal 20 ms of ≤3.5 μV. The AF recurrence rate during 6 months was measured. Results. At the baseline ALP were found in 25 (83%) patients of the control group and in 24 (86%) patients of the spironolactone group (р=0.977). After 6 months treatment the ALP rate was significantly decreased in the spironolactone group (57%, χ2=4.27, р=0.03 compared to the baseline) but remained high in control (80%, χ2=0.00; р=1.0). During 6 months AF recurrences were documented in 5 (18%) participants of the spironolactone group and in 14 (47%) patients of the control one (χ2=4.23; р=0.04). Additional spironolactone intake was associated with 28.8% (95% CI 4.6–48.7) reduction in the AF recurrence. Conclusions. Application spironolactone for 6 months additionaly to standard therapy for patients with paroxysmal AF leads to improving P-wave SAECG, reduction of ALP and AF recurrence.